A Narrative Review on the FSTL-1 Protein and its Current Known Impact in Cardiovascular Ischaemic Disease - José Rodrigues Gomes; Mário Santos (University Library System, University of Pittsburgh, 2024)
Myocardial infarction (MI) is one of the leading causes of death worldwide, and even though modern medicine has reduced considerably the number of deaths due to MI, patients still undergo serious cardiac issues that dramatically affects their well-being. Since the start of the century, massive efforts have been employed in exploring stem cell therapy, however, it is believed that it has failed to live up to expectations and further work must done. Alongside this, FSTL-1 has been an emerging protein which seems to offer a multitude of benefits in post-MI. A considerable number of studies with FSTL-1 have been conducted, always with a very satisfactory level of success, especially considering that research is still in its preliminary phases. In this study, a general evaluation is done to 1) the known mechanisms regulated by FSTL-1, 2) the recognized effects of FSTL-1 in cardiac tissue and cells, 3) and what work can be done to clarify questions and further expand our knowledge in order to advance FSTL-1 as a potential therapeutic agent.